Pengaruh Pestisida Nabati Daun Mimba Terhadap Kutu Beras (Sitophilus oryzae L) Pada Beras Lokal - Ni Nengah Sudarma Yanti; I Gusti Ayu Diah Yuniti; Ni Putu Eka Pratiwi (Agrofarm: Jurnal Agroteknologi, 2022)
Rice is a staple food for most of the population in Indonesia. This study aims to determine the effect of neem leaf plant pesticides on rice lice pests and the optimal optimal concentration of neem leaf pesticides on the development of rice lice pests. This study used a Completely Randomized Design (CRD) with 6 treatments that were repeated 4 times. The design of the study was compiled namely without giving neem leaves (D0 / control), giving neem leaves concentration of 1 gram (D1), giving neem leaves concentration of 2 grams (D2), giving neem leaves concentration of 3 grams (D3), giving neem leaves concentration of 4 gram (D4) and administration of neem leaf concentration of 5 grams (D5). Observations were made on the number of Sitophilus oryzae L. imago mortality and the number of Sitophilus oryzae L. live imago. The results showed that the administration of neem leaf vegetable pesticides on the mortality of rice lice pests was very significant (P <0.01). Concentration of plant leaf pesticides that can inhibit the development of rice flea pests is 5 grams of neem leaf insecticide with 60.00% mortality of Sithophilus oryzae L. after 168 hours application of dried neem leaf insecticide (%).